Answer :

Consider LHS,

LHS =

Multiplying and dividing with (secθ + tanθ),

⇒ = ×

We know that (a + b) (a – b) = a^{2} – b^{2}.

⇒ =

We know that sec^{2}θ - tan^{2}θ = 1.

⇒ =

We know that = secθ and = tanθ.

⇒ = cosθ() + cosθ ()

= 1 + sinθ = RHS

Hence proved.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Trigonometric Identities39 mins

Heights and Distances-I45 mins

Trigonometric Identities-II43 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Prove the followiTamil Nadu Board - Math

If sinθ, cosθ andTamil Nadu Board - Math

Prove the followiTamil Nadu Board - Math

Prove the followiTamil Nadu Board - Math

If x = a secθ + bTamil Nadu Board - Math

Prove the followiTamil Nadu Board - Math

Prove the followiTamil Nadu Board - Math

Prove the followiTamil Nadu Board - Math

Prove the followiTamil Nadu Board - Math

Prove the followiTamil Nadu Board - Math